The personal Luther: essays on the reformer from a cultural historical perspective - Karant-Nunn, Susan C. (St Andrews studies in Reformation history, 2018)
Luther's ego-documents: cultural history and the reconstruction of the historical self -- Luther's conscience: a template for the modern west? -- Luther's friendship with Frederick the Wise -- Luther's relational God, finding a loving heavenly Father -- Fleshly work, the sex act as Christian liberty -- The masculinity of Martin Luther, theory, practicality, and humor -- The tenderness of daughters, the waywardness of sons. Martin Luther as a father -- Martin Luther's heart -- Martin Luther's perfect death -- The imprint of personality upon the Reformation